Infections and Ischemic Stroke Outcome. (28th June 2011) - Grabska, Katarzyna; Gromadzka, Grażyna; Członkowska, Anna
Abstract : Background . Infections increase the risk of ischemic stroke (IS) and may worsen IS prognosis. Adverse effects of in-hospital infections on stroke outcome were also reported. We aimed to study the prevalence of pre- and poststroke infections and their impact on IS outcome. Methods . We analysed clinical data of 2066 IS patients to assess the effect of pre-stroke and post-stroke infections on IS severity, as well as short-term (up to 30 days) and long-term (90 days) outcome. The independent impact of infections on poor outcome (death, death/dependency) was investigated by use of logistic regression analysis. The effect of antibiotic therapy during hospitalization on the outcome was also assessed. Results . Pre-stroke infections independently predicted worse short-term outcome. In-hospital infections were associated with worse short-term and long-term IS prognosis. Antibacterial treatment during hospitalization did not improve patients' outcome. Conclusions . Prevention of infections may improve IS prognosis. The role of antibiotic therapy after IS requires further investigations.